Years of life lost due to deaths of despair and COVID-19 in the United States in 2020: patterns of excess mortality by gender, race and ethnicity - Parker Entrup; Leon Brodsky; Candice Trimble; Stephanie Garcia; Nasra Mohamed; Megan Deaner; J. P. Martell; Julie Teater; Ayana Jordan; Jeanette M. Tetrault; O. Trent Hall (BMC, 2023)
Abstract Background In 2020 COVID-19 was the third leading cause of death in the United States. Increases in suicides, overdoses, and alcohol related deaths were seen-which make up deaths of despair. How deaths of despair compare to COVID-19 across racial, ethnic, and gender subpopulations is relatively unknown. Preliminary studies showed inequalities in COVID-19 mortality for Black and Hispanic Americans in the pandemic's onset. This study analyzes the racial, ethnic and gender disparities in years of life lost due to COVID-19 and deaths of despair (suicide, overdose, and alcohol deaths) in 2020. Methods This cross-sectional study calculated and compared years of life lost (YLL) due to Deaths of Despair and COVID-19 by gender, race, and ethnicity. YLL was calculated using the CDC WONDER database to pull death records based on ICD-10 codes and the Social Security Administration Period Life Table was used to get estimated life expectancy for each subpopulation. Results In 2020, COVID-19 caused 350,831 deaths and 4,405,699 YLL. By contrast, deaths of despair contributed to 178,598 deaths and 6,045,819 YLL. Men had more deaths and YLL than women due to COVID-19 and deaths of despair. Among White Americans and more than one race identification both had greater burden of deaths of despair YLL than COVID-19 YLL. However, for all other racial categories (Native American/Alaskan Native, Asian, Black/African American, Native Hawaiian/Pacific Islander) COVID-19 caused more YLL than deaths of despair. Also, Hispanic or Latino persons had disproportionately higher mortality across all causes: COVID-19 and all deaths of despair causes. Conclusions This study found greater deaths of despair mortality burden and differences in burden across gender, race, and ethnicity in 2020. The results indicate the need to bolster behavioral health research, support mental health workforce development and education, increase access to evidence-based substance use treatment, and address systemic inequities and social determinants of deaths of despair and COVID-19.